Studio Tari Di Pekanbaru Melalui Pendekatan Ekologi Arsitektur - Istiqomah, Istiqomah; Rijal, Muhammad; Hidayat, Wahyu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The traditional dance has preserved and developed in Pekanbaru. Dance as art in Pekanbaru is supported by students and artists, so that it can be developing until now. Dance studio in pekanbaru presented to gather the dance community and as a place for the artists to practice. Therefore, it needed a place that collected the art dance community and dance artist to practice in large numbers. Dance studio was facilitated to all dance activities. The concept of modern building that introduced and demonstrated the dance widely. Dance studio in pekanbaru used eco-architecture themes in design paradigm. The ecology architecture implemented in landscape, interior and building facade. Ecology architecture as approach in the design of the building was produced the concept of eco movement that meant movement & ecology. There were three ways to created room and motion pattern, the line, volume and level. Dance studio in pekanbaru has six mass of buildings which located near to each other, to access all of the buildings, users can be used the connecting bridge. The room at dance studio in pekanbaru had numerous openings luminance space to give the effect of natural lighting and natural atmosphere into the building. There were many open spaces and outdoor classes in dance studio area.Keyword: Dance Studio, Eco Movement, Ecological Architecture